Foundations of education - Caldreon, Jose F. (Manila, 1998)
This book is an answer to an urgent need. There is paucity of references on foundations of education in the graduate level. The author speaks with authority on the matter dure to his long years of teaching Foundations of Education. Hence, this book was written. All the essential information about the subject are adequately discussed. Clear Illustrations are provided for clarification purposes. This is a very good textbook for student taking Foundations of Education in the graduate level and for education students taking Foundations of Education in the collegiate level. This book os divided into six parts, each part dealing with a major foundation of education: psychological, sociological, anthropological, historical, philosophical, and legal foundations. The author does not claim orginality to all the information therein. The author has only sprinkling of original ideas Most of the contents have been borrowed from writings of respected authors on the subject. Hence, to them the author owes deep gratitude. - - Preface
Keywords: Education -- Philippines